The role of collaborative research in learning to incorporate values of the public in social-ecological system governance: case study of bushfire risk planning - Kathryn J. H. Williams (Resilience Alliance, 2020)
Values of the public are a key and dynamic component of bushfire governance SES. Learning to work with these values is a significant challenge for government and environmental managers and an important aspect of policy transition in many contexts. During such transitions, collaborative research can play a key role in social learning, but this may be particularly challenging for agencies with dominant expertise in technical and ecological domains. We examined how collaborative research supported social learning to incorporate values of the public in bushfire governance in the State of Victoria, Australia. Following disruption of a major bushfire, new policy directions were established, including greater attention to expectations and participation of communities in bushfire management. Among other actions, the state environmental agency supported this policy transition by establishing a 3-year research collaboration to better understand and incorporate values of the public in their decision making. As both participants and observers of this research, we analyzed publications, unpublished internal reports, and notes from meetings and workshops to identify how the collaborative research facilitated and constrained learning. Analysis revealed how collaborative research presents interruptions in the form of questioning of plans and routines (including of researchers), joint concept development, collection and sharing of new information, tensions within the research collaboration, idea generation building on research insights, and action research to develop new tools or frameworks. These forms of disruption operated in different ways, involving different groups of actors, levels of collaboration, and opportunities for feedback, and these in turn had implications for the forms of learning that occurred. Collaborative research also identified constraints to learning that, in some instances, set the stage for further learning, for example through capacity building and further research.